A generalization of Minkowski's inequality by Hahn integral operator. Issue 5 (3rd September 2018) - Khan, Hasib; Tunç, Cemil; Alkhazan, Abdulwasea; Ameen, Barakat; Khan, Aziz
ABSTRACT: In this paper, we use the Hahn integral operator for the description of new generalization of Minkowski's inequality. The use of this integral operator definitely generalizes the classical Minkowski's inequality. Our results with this new integral operator have the abilities to be utilized for the analysis of many mathematical problems as applications of the work.